2017
DOI: 10.3389/fnmol.2017.00060
|View full text |Cite
|
Sign up to set email alerts
|

Calpastatin Overexpression Preserves Cognitive Function Following Seizures, While Maintaining Post-Injury Neurogenesis

Abstract: In the adult mammalian brain, new neurons continue to be produced throughout life in two main regions in the brain, the subgranular zone (SGZ) in the hippocampus and the subventricular zone in the walls of the lateral ventricles. Neural stem cells (NSCs) proliferate in these niches, and migrate as neuroblasts, to further differentiate in locations where new neurons are needed, either in normal or pathological conditions. However, the endogenous attempt of brain repair is not very efficient. Calpains are protea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Certain studies have demonstrated that the information from vertebral cells in the hippocampus region may be projected into the cerebral cortex through the cerebral foot and fimbria of the fornix, forming connections among the neurons and a closed loop for learning and memory ( 21 , 22 ). In addition, cell proliferation, migration and differentiation in hippocampus were revealed to be closely associated with spatial and associative learning and memory ( 23 ). Apoptosis is a complex intracellular cascade, with multiple signals and pathways involved in the initiation of cellular apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Certain studies have demonstrated that the information from vertebral cells in the hippocampus region may be projected into the cerebral cortex through the cerebral foot and fimbria of the fornix, forming connections among the neurons and a closed loop for learning and memory ( 21 , 22 ). In addition, cell proliferation, migration and differentiation in hippocampus were revealed to be closely associated with spatial and associative learning and memory ( 23 ). Apoptosis is a complex intracellular cascade, with multiple signals and pathways involved in the initiation of cellular apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have addressed that CAST/calpain system was involved in cell death following glutamate excitotoxicity ( Miao et al, 2012 ; Curcio et al, 2015 ; Yan et al, 2016 ). Calpains are calcium-dependent cysteine proteases, which ubiquitously exist in organisms ( Curcio et al, 2016 ; Machado et al, 2017 ). The activity of calpains are physiologically regulated by its specific endogenous inhibitor, calpastatin (CAST) ( Averna et al, 2001 ; Volbracht et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…Calpains are calcium-dependent proteases involved in neuronal death induced by KA [ 38 , 39 ]. Calpain inhibition through calpastatin, the endogenous inhibitor of calpains, can protect against KA-induced hippocampal neuronal damage and cognitive dysfunction [ 40 ]. Therefore, we examined the effect of asiatic acid on the expression of calpains and calpastatin in KA-treated rats.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, KA treatment results in neuronal damage or death, with associated increased levels of calpains, which are ubiquitously expressed calcium-activated proteases [ 39 , 51 ]. Calpain inhibition has been demonstrated to improve neuronal function and limit neuronal damage in several excitotoxic brain injuries [ 38 , 40 , 44 ]. In the current study, we observed that KA treatment increased the level of calpains and reduced the level of calpastatin, a calpain inhibitor, in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%